Measuring Efficiency of Islamic Banking in Indonesia: Evidence from the DEA during 2021 -2024 - Nuzulia; Hotsawadi, Hotsawadi (Salam (Islamic Economics Journal), 2025)
ABSTRACT The dominance of Islamic banking in the national financial system remains relatively low, with a market share of financial assets of 7.3 percent as of 2023. This study aims to measure the level of efficiency of Islamic banking in Indonesia using the Data Envelopment Analysis (DEA) approach and analyze variations in financial performance between Islamic banks during the 2021–2024 period. The results of the study indicate that the efficiency of Islamic banks in Indonesia remains variable. BTPN Syariah has the highest level of efficiency, followed by Panin Dubai Syariah and Victoria Syariah. On the other hand, Muamalat and Aladin Syariah were recorded as the lowest. Four of the nine Islamic banks have below-average efficiency, including BSI with an efficiency value of 62.55 percent. This shows that the size of assets does not guarantee high efficiency, as efficiency is more determined by the effectiveness of resource management. These findings suggest the need to enhance efficiency through digitalization, optimize resource management, and innovate products and services, enabling Islamic banks to become more competitive and sustainable. Keywords: Data envelopment analysis (DEA), Efficiency, Islamic banking, Sharia Bank Performance